A minimal clinically important difference measured by the Cambridge Pulmonary Hypertension Outcome Review for patients with idiopathic pulmonary arterial hypertension. (1st May 2021) - Bunclark, Katherine; Doughty, Natalie; Michael, Alice; Abraham, Nisha; Ali, Samantha; Cannon, John E; Sheares, Karen; Speed, Nicola; Taboada, Dolores; Toshner, Mark; Pepke‐Zaba, Joanna
Abstract : Several patient‐reported outcome measures have been developed to assess health status in pulmonary arterial hypertension. The required change in instrument scores needed, to be seen as meaningful to the individual, however remain unknown. We sought to identify minimal clinically important differences in the Cambridge Pulmonary Hypertension Outcome Review (CAMPHOR) and to validate these against objective markers of functional capacity. Minimal clinically important differences were established from a discovery cohort ( n  = 129) of consecutive incident cases of idiopathic pulmonary arterial hypertension with CAMPHOR scores recorded at treatment‐naïve baseline and 4–12 months following pulmonary arterial hypertension therapy. An independent validation cohort ( n  = 87) was used to verify minimal clinically important differences. Concurrent measures of functional capacity relative to CAMPHOR scores were collected. Minimal clinically important differences were derived using anchor‐ and distributional‐based approaches. In the discovery cohort, mean (SD) was 54.4 (16.4) years and 64% were female. Most patients (63%) were treated with sequential pulmonary arterial hypertension therapy. Baseline CAMPHOR scores were: Symptoms, 12 (7); Activity, 12 (7) and quality of life, 10 (7). Pulmonary arterial hypertension treatment resulted in significant improvements in CAMPHOR scores ( p  < 0.05). CAMPHOR minimal clinically important differences averaged across methods for health status improvement were: Symptoms, –4 points; Activity, –4 points and quality of life –3 points. CAMPHOR Activity score change ≥minimal clinically important difference was associated with significantly greater improvement in six‐minute walk distance, in both discovery and validation populations. In conclusion, CAMPHOR scores are responsive to pulmonary arterial hypertension treatment. Minimal clinically important differences in pulmonary hypertension‐specific scales may provide useful insights into treatment response in future clinical trials.